Cancer-Mediated Muscle Cachexia: Etiology and Clinical Management. (June 2021) - Siff, Thomas; Parajuli, Parash; Razzaque, Mohammed S.; Atfi, Azeddine
Abstract : Muscle cachexia has a major detrimental impact on cancer patients, being responsible for 30% of all cancer deaths. It is characterized by a debilitating loss in muscle mass and function, which ultimately deteriorates patients' quality of life and dampens therapeutic treatment efficacy. Muscle cachexia stems from widespread alterations in whole-body metabolism as well as immunity and neuroendocrine functions and these global defects often culminate in aberrant signaling within skeletal muscle, causing muscle protein breakdown and attendant muscle atrophy. This review summarizes recent landmark discoveries that significantly enhance our understanding of the molecular etiology of cancer-driven muscle cachexia and further discuss emerging therapeutic approaches seeking to simultaneously target those newly discovered mechanisms to efficiently curb this lethal syndrome. Highlights: Cancer-associated muscle cachexia is a severe muscle-wasting syndrome that occurs in the majority of cancer patients and strongly predicts negative outcomes. The deterioration in muscle function and homeostasis are mediated by a host of tumor-derived circulating factors that converge onto common signaling pathways, leading to the final effect of muscle breakdown. The flurry of experiments conducted in the past decades has largely failed to achieve therapeutic breakthroughs for muscle cachexia. To attain the goal of an effective new treatment, it is now becoming imperative to fully understand not only the factors at play in the development of muscle cachexia and the complex relationships between them, but also why past and current therapeutic endeavors failed to curb this deadly syndrome.